The use of cannabinoids in colitis: a systematic review and meta-analysis - Couch, Daniel G.; Maudslay, Henry; Doleman, Brett; Lund, Jonathan N.; O'Sullivan, Saoirse (Lippincott, Williams & Wilkins, 2018)
Background: Clinical trials investigating the use of cannabinoid drugs for the treatment of intestinal inflammation are anticipated secondary to preclinical literature demonstrating efficacy in reducing inflammation. Methods: We systematically reviewed publications on the benefit of drugs targeting the endocannabinoid system in intestinal inflammation. We collated studies examining outcomes for metaanalysis from EMBASE, MEDLINE and Pubmed until March 2017. Quality was assessed according to mSTAIR and SRYCLE score. Results: From 2008 papers, 51 publications examining the effect of cannabinoid compounds on murine colitis, and two clinical studies were identified. 24 compounds were assessed across 71 endpoints. Cannabidiol, a phytocannabinoid, was the most investigated drug. Macroscopic colitis severity (disease activity index - DAI) and myeloperoxidase activity (MPO) were assessed throughout publications and were meta-analysed using random effects models. Cannabinoids reduced DAI in comparison with vehicle; SMD -1.36, 95% CI -1.62 to-1.09, I²=61%). FAAH inhibitor URB597 had the largest effect size (SMD-4.43, 95% CI-6.32,-2.55), followed by the synthetic drug AM1241 (SMD–3.11, 95% CI -5.01, -1.22) and the endocannabinoid anandamide (SMD-3.03, 95% CI -4.89,-1.17, I² not assessed). Cannabinoids reduced MPO in rodents compared to vehicle; SMD -1.26, 95% CI-1.54 to -0.97, I²=48.1%. Cannabigerol had the largest effect size (SMD -6.20, 95%CI-9.90, -2.50), followed by the synthetic CB₁ agonist ACEA(SMD -3.15, 95%CI-4.75, -1.55) and synthetic CB₁/₂ agonist WIN55,212-2(SMD-1.74, 95%CI-2.81, -0.67, I²=57%). We found no evidence of reporting bias. No significant difference was found between the prophylactic and therapeutic use of cannabinoid drugs. Conclusions: There is abundant pre-clinical literature demonstrating the anti-inflammatory effects of cannabinoid drugs in inflammation of the gut. Larger randomised controlled-trials are warranted.